VASEKTOMI PADA MONYET EKOR PANJANG (MACACA FASCICULARIS)DI LOKASI WISATA SANGEH - WANDIA. I .N; I K. SUATHA; I G. SOMA; S. K. WIDYASTUT; A.L.T. ROMPIS; I P. G. YUDHI ARJENTINIA (Buletin Udayana Mengabdi, 2009)
ABSTRACT Growth population control on the animal population dwelling a restricted habitat is very important to decrease, especially the negative impact on its surrounding environment. This Community Service was conducted as an application of vasectomy on an adult male of long tailed macaque occupying the tourist destination of Sangeh. This was the choosen method to overcome the overcrowded population. Vasectomy is surgical division of all or part of the vas deferens to induce sterility. One selected adult male monkey was anesthetized successfully using blowpipe. Surgical resection of part of vas deferens used a bilateral slicing method. Vasectomy was fully done nearly in one hour, and the monkey was released to habitat in the following three days of captivity.